Love in the drug war : selling sex and finding Jesus on the Mexico-US border - Luna, Sarah (University of Texas Press, 2020)
"This book looks at sex workers in "la zona," a walled area within Reynosa (the Mexican side of the border), and the missionaries who came to Reynosa to "rescue" them. The relationship between the sex workers and the missionaries intensified and became more complex as the drug war in Reynosa escalated in 2008-2009. The author sees the border as a place that creates value for both groups, rather than being solely a barrier, and indicates that both groups chose to migrate there for the sex industry. The gendered obligations between sex workers and missionaries, sex workers and their families, missionary workers and God, and sex workers and drug cartels all feed into her analysis of "value," which leads to interesting discussions of non-sovereignty (the interconnectedness we all have but can't necessarily control), among other theoretical concepts"--